Pengaruh Disiplin Kerja dan Jenjang Karir terhadap Produktivitas Kerja Pegawai Alfamart pada Generasi Milenial di Kabupaten Bima - Sahdan maulana; Rahmatia; Firman kusumayadi (Tamilis Synex: Multidimensional Collaboration, 2026)
Employee productivity is a crucial factor in determining organizational performance, particularly in the highly competitive retail industry. This study aims to examine the influence of work discipline and career path on the work productivity of millennial employees at Alfamart in Bima Regency. A quantitative approach with an associative research design was employed to analyze the relationships among variables. Data were collected through questionnaires using a five-point Likert scale from 30 millennial employees, selected using an unknown population sampling approach. The collected data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, coefficient of determination, and hypothesis testing through t and F tests with IBM SPSS version 23. The findings reveal that work discipline has a positive and significant effect on employee productivity (t = 3.513; p = 0.002). Career path also demonstrates a positive and significant influence on productivity (t = 4.540; p = 0.000). Simultaneously, work discipline and career path significantly affect employee productivity (F = 103.014; p = 0.000), with a coefficient of determination (R²) of 0.884, indicating that 88.4% of the variation in employee productivity is explained by these two variables. The results suggest that strengthening work discipline and providing clear career advancement opportunities are effective strategies for improving the productivity of millennial employees in the retail sector.